Preparation method and application of porous solid electrolyte
A simplified method for preparing porous solid electrolytes using MOF materials as pore-formers and seeds for alkali metal electrodes addresses inefficiencies in existing methods, enhancing ion migration and electrode activity while reducing costs.
Patent Information
- Application Number
- CN202411234908.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-04
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-09-04
AI Technical Summary
Existing methods for preparing porous solid electrolytes are inefficient and costly due to requiring multiple steps, including complex processes like magnetron sputtering and atomic layer deposition for surface treatment, which limits their practical application in high-capacity alkali metal batteries.
A method involving mixing MOF materials with solid electrolyte powder in an inert solvent, forming a mixed powder, pressing, and sintering to create a porous solid electrolyte with a three-dimensional network structure, using the MOF's organic shell as a pore-forming agent and metal core as a seed for alkali metal electrode integration, eliminating the need for additional surface treatments.
This method enhances ion migration efficiency, improves active material utilization, and stabilizes high-current density cycling by creating a porous structure with a simplified process, reducing costs and increasing the electrochemical activity of alkali metal electrodes.
Smart Images

Figure CN119253033A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of electrochemical technology, and more specifically, relates to a preparation method of a porous solid electrolyte and an application thereof. Background Art
[0002] Lithium-ion batteries are a low-cost, long-life, high-efficiency rechargeable battery technology that is widely used in mobile phones, laptops, electric vehicles, and large-scale energy storage systems. However, their energy density and safety can no longer meet the needs of electric vehicles for high mileage and high safety. In contrast, solid-state alkali metal batteries use high-capacity, low-voltage alkali metals as negative electrodes, which are expected to significantly increase battery energy density. At the same time, solid-state alkali metal batteries replace flammable organic electrolytes with non-flammable solid electrolytes to fundamentally solve battery safety issues. For solid electrolytes, compared with planar solid electrolytes, porous solid electrolytes can improve the utilization rate of active materials in alkali metal negative electrodes and achieve stable cycling of solid-state batteries at high current density and surface capacity. Therefore, it is of great significance to study a method for preparing porous solid electrolytes.
[0003] The existing preparation methods of porous solid electrolytes often form a three-dimensional network structure by forming pores with a pore-forming agent, and then perform surface treatment on the three-dimensional network structure to increase its affinity for the alkali metal negative electrode, thereby facilitating the subsequent composite process with the alkali metal negative electrode. However, the entire process requires two steps to be implemented, and the process of surface treatment of the three-dimensional network structure often requires the use of more complex processes such as magnetron sputtering and atomic layer deposition, resulting in low preparation efficiency and high cost. Summary of the invention
[0004] In view of the above defects or improvement needs of the prior art, the present invention provides a method for preparing a porous solid electrolyte and its application, the purpose of which is to provide a method for preparing a porous solid electrolyte with low cost and high efficiency.
[0005] In order to achieve the above object, in a first aspect, the present invention provides a method for preparing a porous solid electrolyte, comprising:
[0006] The MOF material and the solid electrolyte powder are uniformly mixed in an inert solvent, and the inert solvent is evaporated to obtain a mixed powder A;
[0007] The mixed powder A is spread on the solid electrolyte powder and pressed to form a green billet; the green billet is sintered to obtain a porous solid electrolyte with one side being porous.
[0008] Further preferably, the MOF material is: a mesh metal organic framework material, a zeolite imidazole framework material, a Levahill framework material or a pore channel framework material.
[0009] Further preferably, the solid electrolyte powder is garnet-type oxide, β″-alumina, NASICON-type solid electrolyte powder, argyrodite-type solid electrolyte powder, alkali metal nitride or LiPON-type solid electrolyte powder.
[0010] Further preferably, the mass ratio of the MOF material and the solid electrolyte powder mixed in the inert solvent is 1:1 to 1:5.
[0011] More preferably, the sintering temperature is 500°C to 1700°C.
[0012] In a second aspect, the present invention provides a porous solid electrolyte prepared by the method for preparing the porous solid electrolyte provided in the first aspect of the present invention.
[0013] In a third aspect, the present invention provides a method for preparing a solid-state alkali metal battery negative electrode, comprising:
[0014] The porous side of the porous solid electrolyte is brought into contact with an alkali metal material in a molten state, thereby inducing the molten alkali metal material to fill the pores in the porous solid electrolyte, thereby forming a composite solid alkali metal battery negative electrode in which the solid electrolyte and the alkali metal material permeate each other;
[0015] Wherein, the porous solid electrolyte is the porous solid electrolyte provided by the second aspect of the present invention.
[0016] More preferably, the temperature of the alkali metal material in a molten state is 150°C to 500°C.
[0017] In a fourth aspect, the present invention provides a porous solid electrolyte negative electrode, which is prepared by the method for preparing a solid alkali metal battery negative electrode provided by the third aspect of the present invention.
[0018] In a fifth aspect, the present invention provides a solid-state alkali metal battery, whose negative electrode is the porous solid electrolyte negative electrode provided by the fourth aspect of the present invention.
[0019] In general, the above technical solutions conceived by the present invention can achieve the following beneficial effects:
[0020] 1. The present invention provides a method for preparing a porous solid electrolyte, wherein the MOF material and the solid electrolyte powder are uniformly mixed in an inert solvent, and the inert solvent is evaporated to obtain a mixed powder A; the mixed powder A is spread on the solid electrolyte powder for pressing to form a biscuit; the biscuit is sintered so that the mixed powder A forms a strong bond with the high-density solid electrolyte powder to form a porous solid electrolyte with one side being porous. The present invention uses the organic shell in the MOF material as a pore-forming agent, and after the mixed powder A and the solid electrolyte powder are pressed and sintered, the metal core of the MOF material is transformed into a metal element or a corresponding metal oxide, which is attached to the surface of the formed pores to form a three-dimensional network structure, and the metal core of the MOF material in the obtained porous solid electrolyte can be directly used as a seed to induce the alkali metal negative electrode to compound with it, without the need to use an additional complex process to perform surface treatment on the three-dimensional network structure, and the preparation efficiency is high and the cost is low.
[0021] 2. The method for preparing the porous solid electrolyte provided by the present invention and the prepared porous solid electrolyte with a three-dimensional network structure can solve the problems of low negative electrode ion migration depth, only alkali metal near the interface having electrochemical activity, and poor interface wettability when the solid electrolyte with a planar structure is combined with an alkali metal negative electrode. It can significantly improve the ion migration efficiency in the negative electrode, reduce the charge transfer energy barrier, improve the utilization rate of active materials in the alkali metal negative electrode, and realize stable circulation of solid-state batteries at high current density and surface capacity.
[0022] 3. The present invention provides a method for preparing a negative electrode of a solid-state alkali metal battery. The metal core of the MOF material is used as a seed to induce the alkali metal material to composite with the porous side of a porous solid electrolyte. The metal core in the MOF material can form a single substance or an oxide under high temperature and serve as a nucleation center to induce the alkali metal material to fill the pores of the porous solid electrolyte, thereby increasing the active area of the electrochemical reaction and improving the charge transfer rate. The entire process is simple, the preparation efficiency is high, and the cost is low. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 A flow chart of a method for preparing a porous solid electrolyte provided by the present invention;
[0024] Figure 2 This is a schematic diagram of the morphology of the Ag-MOF material obtained in an embodiment of the present invention;
[0025] Figure 3 A schematic diagram of the SEM morphology of the porous LLZTO loaded with Ag nanoparticles provided in an embodiment of the present invention;
[0026] Figure 4 A critical current density diagram of porous LLZTO prepared with solid electrolyte powder and pore-forming agent in different mass ratios provided in an embodiment of the present invention;
[0027] Figure 5 A schematic diagram of the SEM morphology of porous LLZTO after the molten Li metal material provided in an embodiment of the present invention is filled into the pores;
[0028] Figure 6 The lithium symmetric battery assembled from the obtained solid-state Li metal battery negative electrode provided in the embodiment of the present invention has a current density of 1 mA cm -2 Cycle performance diagram below;
[0029] Figure 7 A rate performance diagram of a lithium iron phosphate full battery assembled from the obtained solid-state Li metal battery negative electrode provided in an embodiment of the present invention;
[0030] Figure 8 The present invention provides a charge and discharge curve at different rates of a lithium iron phosphate full battery assembled from the obtained solid-state Li metal battery negative electrode. DETAILED DESCRIPTION
[0031] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0032] In order to achieve the above-mentioned object, in a first aspect, the present invention provides a method for preparing a porous solid electrolyte, such as Figure 1 As shown, including:
[0033] The MOF (metal organic framework) material and the solid electrolyte powder are uniformly mixed in an inert solvent, and the inert solvent is evaporated to obtain a mixed powder A;
[0034] The mixed powder A is spread on the solid electrolyte powder and pressed to form a green billet; the green billet is sintered to obtain a porous solid electrolyte with one side being porous.
[0035] It should be noted that after sintering, the metal core of the MOF material is transformed into a metal element or the corresponding metal oxide, which is attached to the surface of the porous solid electrolyte framework. The organic shell in the MOF material can act as a pore former to regulate the pore size, number and distribution in the porous solid electrolyte and construct a network structure. The network-like porous solid electrolyte can significantly improve the ion migration efficiency in the negative electrode, reduce the charge transfer energy barrier, and improve the utilization rate of the negative electrode active material.
[0036] In an optional embodiment, the MOF material can be: a reticulated metal organic framework material (IRMOFs), a zeolite imidazole framework material (ZIFs), a Levahill framework material (MILs), a pore channel framework material (PCNs), and the like.
[0037] In an optional embodiment, a solvothermal method can be used to prepare MOF materials: nitrate is dissolved in anhydrous methanol to obtain solution A; 2-aminoterephthalic acid is dissolved in dimethylformamide (DMF) to obtain solution B; then solution B is mixed with solution A and subjected to hydrothermal reaction to synthesize the corresponding MOF material. Among them, the nitrate is preferably AgNO3, Zn(NO3)2, Fe(NO3)3, CuNO3, Mg(NO3)2, Al(NO3)3, Sn(NO3)4, Pb(NO3)2 and other nitrates, and MOF materials with different metal cores are synthesized.
[0038] In an optional embodiment, the solid electrolyte powder is preferably a solid electrolyte powder that is chemically stable with alkali metals, such as garnet-type oxide, β″-alumina, NASICON-type solid electrolyte powder, argyrodite-type solid electrolyte powder, alkali metal nitride, and LiPON-type solid electrolyte powder.
[0039] In an optional embodiment, the mass ratio of the MOF material and the solid electrolyte powder mixed in the inert solvent is 1:1 to 1:5.
[0040] In an optional embodiment, the sintering temperature is 500°C to 1700°C.
[0041] In an alternative embodiment, the inert solvent may be isopropanol, n-heptane, toluene, benzene, xylene, carbon disulfide, or the like.
[0042] In order to further illustrate the preparation method of the porous solid electrolyte provided by the present invention, the following is described in detail with reference to specific embodiments:
[0043] This embodiment provides a porous garnet solid electrolyte (Li 6.4 LqCy 1.4 Ta 0.6 O 12 , LLZTO) preparation method, specifically comprising the following process:
[0044] Preparation of MOF materials:
[0045] In this embodiment, taking AgNO3 as nitrate as an example, 1mmolAgNO3 was dissolved in 50mL anhydrous methanol to obtain solution A; 1mmol 2-aminoterephthalic acid was dissolved in 10mL DMF solution to obtain solution B; then solution B was slowly added dropwise to solution A using a syringe pump. Subsequently, the mixture was transferred to a 100ml stainless steel reactor with a Teflon liner, sealed, and heated at 120°C for 12h. The precipitate was collected by centrifugation, washed alternately with DMF and ethanol three times, and dried in a vacuum oven at 60°C overnight to obtain an Ag-MOF material, such as Figure 2 shown.
[0046] Preparation of porous solid electrolytes:
[0047] The MOF material and the solid electrolyte powder are mixed and stirred evenly in an inert solvent, and the inert solvent is evaporated to obtain a mixed powder A. The solid electrolyte powder B and the mixed powder A are sequentially added to a tablet pressing mold for pressing to obtain a green blank, and the green blank is sintered at a high temperature to obtain a porous solid electrolyte.
[0048] In this embodiment, Ag-MOF material and solid electrolyte powder LLZTO are mixed and stirred in a n-heptane solvent at a mass ratio of 1:2, and the solvent is evaporated to obtain mixed powder A. 0.1g of LLZTO powder and 0.05g of mixed powder A are added to a tableting mold in sequence, and tablets are pressed at 300MPa to obtain a green blank. The green blank is sintered at 1250°C for 20 minutes to obtain porous LLZTO. The organic shell of Ag-MOF decomposes at high temperature, leaving pores, which helps to construct a porous LLZTO network. The Ag metal core forms a single Ag particle loaded on the surface of the porous LLZTO, such as Figure 3 shown.
[0049] In addition, the present invention also compares the performance of porous LLZTO prepared by solid electrolyte powder LLZTO and MOF material (pore former) in different mass ratios through different embodiments, and obtains the following results as shown in Table 1 and Figure 4 The results shown in Table 1 are the critical current density data of porous LLZTO prepared by solid electrolyte powder and pore-forming agent with different mass ratios provided in the embodiments of the present invention and the critical current density data when the pore-forming agent is replaced by Sn-MOF; Figure 4 The critical current density diagram of porous LLZTO prepared with different mass ratios of solid electrolyte powder and pore-forming agent. From Table 1 and Figure 4 It can be seen that compared with the control example without pore-forming agent, the performance of the examples with pore-forming agent is improved. When the mass ratio of solid electrolyte powder to MOF material is 2:1, the critical current density is the highest, reaching 1.2 mA cm -2, indicating that the porous LLZTO has the strongest ability to inhibit dendrite growth under this condition. In addition, when Ag-MOF is replaced by Sn-MOF, the critical current density of the prepared porous LLZTO can still be increased to 0.9 mA cm -2 , indicating that this method is universal.
[0050] Table 1
[0051] Solid electrolyte Pore forming agent Quality Ratio <![CDATA[Critical current density of symmetric battery (mA cm -2 )]]> Example 1 <![CDATA[Ii 6.4 La3Zr 1.4 Yes 0.6 Oh 12 ]]> Ag-MOF 1:1 0.5 Example 2 <![CDATA[Ii 6.4 La3Zr 1.4 Yes 0.6 Oh 12 ]]> Ag-MOF 2:1 1.2 Example 3 <![CDATA[Li 6.4 La3Zr 1.4 Yes 0.6 Oh 12 ]]> Ag-MOF 3:1 0.6 Example 4 <![CDATA[Li 6.4 La3Zr 1.4 Yes 0.6 Oh 12 ]]> Ag-MOF 5:1 0.3 Example 5 <![CDATA[Li 6.4 La3Zr 1.4 Yes 0.6 Oh 12 ]]> Ag-MOF 6:1 0.1 Example 6 <![CDATA[Li 6.4 La3Zr 1.4 Yes 0.6 oh 12 ]]> Sn-MOF 2:1 09 Comparative Example <![CDATA[Li 6.4 La3Zr 1.4 Yes 0.6 Oh 12 ]]> none 1:0 0.2
[0052] It should be noted that this embodiment only uses LLZTO as a representative of solid electrolyte powder for illustration, and the performance of other solid electrolyte powders is similar to that of LLZTO, which will not be described in detail here.
[0053] In a second aspect, the present invention provides a porous solid electrolyte prepared by the method for preparing the porous solid electrolyte provided in the first aspect of the present invention.
[0054] The related technical scheme is the same as the method for preparing the porous solid electrolyte provided in the first aspect of the present invention, and will not be described in detail here.
[0055] In an optional embodiment, the temperature of the alkali metal material in a molten state is 150°C to 500°C.
[0056] It should be noted that the above-mentioned alkali metal material can be an alkali metal material such as Li, Na, K, Cs, etc.
[0057] It should be noted that after the porous side of the porous solid electrolyte contacts the alkali metal material in the molten state, the metal element or the corresponding metal oxide in the pores of the porous solid electrolyte undergoes an alloying reaction or a replacement reaction with the alkali metal material, inducing the molten alkali metal material to fill the pores in the porous solid electrolyte, forming a composite negative electrode in which the solid electrolyte and the alkali metal material permeate each other, that is, a solid alkali metal battery negative electrode. Among them, when the pores of the porous solid electrolyte are metal elements, the metal elements undergo an alloying reaction with the alkali metal material; when the pores of the porous solid electrolyte are metal oxides, the metal oxides undergo a replacement reaction with the alkali metal material, and may further undergo an alloying reaction.
[0058] The present invention uses the metal core of the MOF material as a seed to induce the alkali metal material to composite with the porous solid electrolyte. The metal core in the MOF material can form a single substance or an oxide under high temperature, which serves as a nucleation center to induce the alkali metal material to fill the pores of the porous solid electrolyte, thereby increasing the active area of the electrochemical reaction and improving the charge transfer rate.
[0059] In order to further illustrate the preparation method of the solid-state alkali metal battery negative electrode provided by the present invention, the LLZTO obtained in the above-mentioned preparation method of the porous solid electrolyte is used as the porous solid electrolyte, and Li metal is used as the alkali metal material as an example, and the specific description is as follows:
[0060] The porous side of the LLZTO obtained in the preparation method of the porous solid electrolyte is contacted with the metallic lithium melted at 200°C to induce an alloying reaction, so that the molten lithium fills the pores in the porous LLZTO, forming a morphology in which the metallic lithium and the porous LLZTO network permeate each other, and a solid-state Li metal battery negative electrode is obtained, such as Figure 5 shown.
[0061] The lithium symmetric battery assembled from the obtained solid-state Li metal battery anode was subjected to a charge transfer reaction at 1 mA cm -2 The cycle performance test was carried out under Figure 6 The cycling performance diagram shown in the figure can be seen that the lithium symmetric battery can be stably cycled for more than 950h with a polarization of 25mV, indicating that the porous LLZTO network can significantly promote the lithium ion conduction of the negative electrode, reduce the Li concentration gradient, and thus inhibit the formation of dendrites.
[0062] The rate performance of the lithium iron phosphate full battery assembled from the obtained solid-state Li metal battery negative electrode was tested, and the following results were obtained: Figure 7 The rate performance diagram shown in the figure shows that at 0.1, 0.2, 0.5, 1.0 and 2.0C, the battery capacities are 155.9, 154.9, 149.2, 136.9 and 119 mAh g -1 When the rate returns to 0.1C, the discharge capacity can be restored to 153.8 mAh g -1 , indicating that the porous LLZTO network provides a stable ion percolation pathway, increases the anode ion migration depth, improves the electrode reaction kinetics, and relieves the anode stress / strain, thus achieving excellent rate performance.
[0063] The charge and discharge performance of the lithium iron phosphate full battery assembled from the obtained solid-state Li metal battery negative electrode was tested at different rates, and the following results were obtained: Figure 8 The charge and discharge curve is shown in the figure; it can be seen from the figure that even at a high rate of 2C, the battery still maintains a stable voltage curve, indicating that the obtained solid-state Li metal battery negative electrode has a high structural stability.
[0064] In a third aspect, the present invention provides a method for preparing a solid-state alkali metal battery negative electrode, comprising:
[0065] The porous side of the porous solid electrolyte is brought into contact with an alkali metal material in a molten state, thereby inducing the molten alkali metal material to fill the pores in the porous solid electrolyte, thereby forming a composite solid alkali metal battery negative electrode in which the solid electrolyte and the alkali metal material permeate each other;
[0066] The porous solid electrolyte is the porous solid electrolyte provided in the second aspect of the present invention. The related technical scheme is the same as the porous solid electrolyte provided in the second aspect of the present invention, and will not be described in detail here.
[0067] In a fourth aspect, the present invention provides a porous solid electrolyte negative electrode, which is prepared by the method for preparing a solid alkali metal battery negative electrode provided by the third aspect of the present invention.
[0068] The related technical scheme is the same as the method for preparing the solid-state alkali metal battery negative electrode provided in the third aspect of the present invention, and will not be described in detail here.
[0069] In a fifth aspect, the present invention provides a solid-state alkali metal battery, whose negative electrode is the porous solid electrolyte negative electrode provided by the fourth aspect of the present invention.
[0070] The related technical solution is the same as the porous solid electrolyte negative electrode provided in the fourth aspect of the present invention, and will not be described in detail here.
[0071] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a porous solid electrolyte, characterized in that: include: The MOF material and the solid electrolyte powder are uniformly mixed in an inert solvent, and the inert solvent is evaporated to obtain a mixed powder A; The mixed powder A is spread on the solid electrolyte powder and pressed to form a green billet; the green billet is sintered to obtain a porous solid electrolyte with one side being porous.
2. The method for preparing a porous solid electrolyte according to claim 1, characterized in that: The MOF material is: a mesh metal organic framework material, a zeolite imidazole framework material, a Levahill framework material or a pore channel framework material.
3. The method for preparing a porous solid electrolyte according to claim 1, characterized in that: The solid electrolyte powder is garnet-type oxide, β″-alumina, NASICON-type solid electrolyte powder, argyrodite-type solid electrolyte powder, alkali metal nitride or LiPON-type solid electrolyte powder.
4. The method for preparing a porous solid electrolyte according to any one of claims 1 to 3, characterized in that: The mass ratio of the MOF material and the solid electrolyte powder mixed in the inert solvent is 1:1 to 1:
5.
5. The method for preparing a porous solid electrolyte according to any one of claims 1 to 3, characterized in that: The sintering temperature is 500℃~1700℃.
6. A porous solid electrolyte, characterized in that: The porous solid electrolyte is prepared by the preparation method of any one of claims 1 to 5.
7. A method for preparing a solid-state alkali metal battery negative electrode, characterized in that: include: The porous side of the porous solid electrolyte is brought into contact with an alkali metal material in a molten state, thereby inducing the molten alkali metal material to fill the pores in the porous solid electrolyte, thereby forming a composite solid alkali metal battery negative electrode in which the solid electrolyte and the alkali metal material permeate each other; Wherein, the porous solid electrolyte is the porous solid electrolyte described in claim 6.
8. The method for preparing a solid-state alkali metal battery negative electrode according to claim 7, characterized in that: The temperature of the alkali metal material in the molten state is 150°C to 500°C.
9. A porous solid electrolyte negative electrode, characterized in that: The solid-state alkali metal battery negative electrode is prepared by the method for preparing the solid-state alkali metal battery negative electrode according to claim 7 or 8.
10. A solid-state alkali metal battery, characterized in that: The negative electrode is the porous solid electrolyte negative electrode as claimed in claim 9.
Citation Information
Patent Citations
Preparation method of porous solid electrolyte for lithium ion battery
CN110137564A
Preparation method of all-solid-state electrolyte battery and all-solid-state electrolyte battery
CN110931848A
Preparation method of ultrathin compact electrolyte of solid oxide battery, and ultrathin compact electrolyte obtained by preparation method
CN112768737A
Modified NASICON type solid electrolyte, composite solid electrolyte ceramic, preparation method of modified NASICON type solid electrolyte and all-solid-state battery
CN118040023A
Solid electrolyte, preparation method thereof, secondary battery, battery module, battery pack and electric device
CN118352610A